Enhanced self-healing performance of graphene oxide/vitrimer nanocomposites: A molecular dynamics simulations study. (7th October 2020) - Park, Chanwook; Kim, Geonwoo; Jung, Jiwon; Krishnakumar, Balaji; Rana, Sravendra; Yun, Gun Jin
Abstract: In this paper, we elucidate the filler effect of the vitrimer nanocomposites in the atomistic aspect for the first time with the molecular dynamics (MD) simulations. The self-healing properties are compared between GO/vitrimer nanocomposites and pristine vitrimers by the self-healing simulation containing the bond exchange reaction algorithm. The results reveal that GO reduces the vitrimers' T g as well as the nanocomposites self-heal better than the vitrimers at all temperature ranges: temp. higher than T g of both, temp. between the two T g s, and temp. lower than T g of both. Atomistic investigations demonstrate that the number of new disulfide bonds that emerged during the self-healing simulation increases in GO/vitrimer nanocomposites, which corroborates adding GO into the vitrimer stimulates the bond exchange reaction. Moreover, our simulation results imply that diverse nanofillers can be adopted for the same purpose. Graphical abstract: Image 1 Highlights: Bond exchange reaction of disulfide-type vitrimers is realized in molecular dynamics simulations. Introducing graphene oxide into the vitrimer reduces the glass transition temperature. Graphene oxide/vitrimer nanocomposites are better self-healed than vitrimers. Results are validated from the bond count of new disulfide bonds created during the self-healing simulations.